The Effect of Ease of Access, Service, and Promotion Strategy on Consumer Decisions in Using BRIlink Chancell Rantauprapat Services - Umi Nofia Friska; Elvina Elvina; Mulkan Ritonga (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research is motivated by the importance of identifying factors driving public interest in using banking agents amidst increasingly tight financial services competition. The purpose of the study is to analyze the influence of ease of access, service, and promotional strategies on consumer decisions in using BRILink Chancell Rantauprapat services. Using a quantitative approach with multiple linear regression analysis methods, the results of the study indicate that partially, ease of access and service do not have a significant influence because they are considered as basic facility standards by consumers. In contrast, promotional strategies were found to be the main determinant factor with the strongest and most significant influence ($p = 0.001$). Simultaneously, these three variables contributed 61.9% to consumer decisions, while the remaining 38.1% was influenced by other factors outside this research model.